Microalbuminuria and spot protein creatinine ratio in early pregnancy as a predictor of preeclampsia - B. M., Rupakala; Sudha, Gajjala Sai; M. P. A., Sai Lakshmi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Hypertensive disorders complicate 5-10% of all the pregnancies and preeclampsia is identified in 3.9%.Preeclampsia is a pregnancy specific syndrome characterized by the development of hypertension and proteinuria in the second trimester of the pregnancy. Microalbuminuria and elevated spot protein creatinine ratio are commonly found in preeclampsia. The aim of this study was to determine microalbuminuria and spot creatinine ratio in early pregnancy as predictors of pre-eclampsia. Methods: The study was conducted among 102 pregnant women by detecting the levels of albuminuria and spot protein creatinine ratio at 10-14 weeks period of gestation. Random urine sample of about 5 ml was taken to analyse the samples for microalbuminuria and spot protein creatinine ratio. All the women included in the study were followed up till delivery to rule out the possibility of developing preeclampsia depending on their microalbumin and spot protein creatinine ratio values. Results: Pregnant women who developed preeclampsia or eclampsia had significantly higher levels of microalbumin and spot protein creatinine ratio. Conclusions: A detailed study among a larger group of population is required to determine that microalbuminuria and spot protein creatinine ratio in early pregnancy are definitive predictors of preeclampsia.